化粧品原料の皮膚一次刺激性試験法の比較研究 培養細胞試験 - NAKANO Eiji; TSUTSUMI Masako; KOIZUMI Yoshio; HOUNOKI Susumu; NAGURA Toshiaki; IGARASHI Atsuko (Skin research, 1984)
We examined polyols (propylene glycol, 1, 3-butylene glycol and glycerin) using cultured cell toxicity test. The members of this study were 6 researchers in the different 3 cosmetic companies. We performed this test with the same procedure in each laboratory. JTC-17 strain was served for this study. We took the following results; the cell toxicity order of three polyols was 1, 3-butylene glycol > propylene glycol >> glycerin. グリセリン, プロピレングリコール, 1, 3-ブチレングリコールの細胞障害性をヒト皮膚由来培養細胞株JTC-17を用いて3施設で試験した。その結果, 細胞障害性の順位は1, 3-ブチレングリコール>プロピレングリコール>>グリセリンであった。細胞障害性の要因の1つに浸透圧が考えられるため, 試験液の浸透圧測定を行ったが, その結果からは浸透圧の大きさが多価アルコールの細胞障害性の主たる原因とは推測し得なかった。